2009
DOI: 10.1590/s1516-35982009000200007
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin-like growth factor I (IGF-I) microsatellite polymorphisms and important economic traits in pigs

Abstract: -This study investigated the association between IGF-I microsatellite marker in an F 2 population (N=459) generated by mating of native boars to Brazilian commercial sows with performance, carcass cut, and meat quality traits.Association analyses were carried out using a statistical model that included genotype, sex, and group as fixed effects and sire as random effect. The IGF-I genotypes were significantly associated with different quantitative traits and these results corroborate with previous QTL analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…Among barrows, Duroc showed an improved performance compared with Piau crossbred, but did not differ from Pietrain crossbred pigs. When univariate studies approaching the original variables were employed, similar results were observed (Faria et al, 2009;Bertol et al, 2013). Pietrain pigs have lower growth rate and slaughter weight compared with Duroc pigs (Bertol et al, 2013).…”
Section: Effects Of Genetic Group Nutritional Plan and Sex On Latent ...supporting
confidence: 52%
“…Among barrows, Duroc showed an improved performance compared with Piau crossbred, but did not differ from Pietrain crossbred pigs. When univariate studies approaching the original variables were employed, similar results were observed (Faria et al, 2009;Bertol et al, 2013). Pietrain pigs have lower growth rate and slaughter weight compared with Duroc pigs (Bertol et al, 2013).…”
Section: Effects Of Genetic Group Nutritional Plan and Sex On Latent ...supporting
confidence: 52%
“…Moreover, the discrepancy from each paternal breed that was used in the present study to compose the genetic groups affected the performance traits. Duroc pigs have a high BW gain as one of the main characteristics of the breed (Wood et al, 2004), while Pietrain pigs have a low feed intake (Bertol et al, 2013) compared to other genetically improved breeds, and the Piau breed is mainly characterized by its slow growth rate (Faria et al, 2009;Peixoto et al, 2009). The low feed intake of Pietrain compared to Duroc crossbred gilts is due to the selection process for a low feed conversion rate and high lean growth that Pietrain has undergone, which has negatively impacted their voluntary intake (Bertol et al, 2013).…”
Section: Giltsmentioning
confidence: 99%
“…However, our results were inconsistent with the study of Amills et al [ 38 ], who suggested that polymorphism of the IGF-I gene led to differences in gene expression. In swine, the IGF-I microsatellite may be located at the 5′ region of the gene close to the promoter region and linked to some other loci in the same chromosome region, which is responsible for the effect on growth traits [ 39 ]. Perhaps the difference in BW among IGF-I genotypes in this study is due to a linkage with other loci in the same chromosome region.…”
Section: Resultsmentioning
confidence: 99%